Optimization of in vivo antimalarial efficacy of combinations of aqueous leaf extracts of Artemisia annua L., Vernonia amygdalina Del, and Microglossa pyrifolia (Lam.) Kuntze using factorial design - Jimmy R. Angupale; Clement O. Ajayi; Jonans Tusiimire; Ndidi C. Ngwuluka (BMC, 2024)
Abstract Background Malaria continues to be among the leading causes of mortality in Africa including Uganda, with the emergence of parasite resistance to the first-line therapeutics (Artemisinin- based Combination Therapy). To find new therapeutics, this study has reported an in vivo antimalarial efficacy of combinations of Artemisia annua (Aa), Vernonia amygdalina (Va), and Microglossa pyrifolia (Mp) in mice model using factorial design. Methods The Aa and Va were extracted by hot infusion, and Mp by cold maceration using distilled water. The dry extracts were screened for different phytochemicals, and later subjected to in vivo antimalarial activity using Peter's 4-day suppressive test. The 23 factorial design used Aa, Va, and Mp aqueous extracts as independent variables at two levels (-1 and 1), and the percentage chemo suppression and survival time as response variables. The data was analyzed using Design Expert 13 and GraphPad Prism employing ANOVA linear regression modelling and t-test respectively. Results All the extracts had alkaloids, phenols, saponins, terpenoids, cardiac glycosides, tannins, steroids, and carbohydrates. The various combinations showed chemo suppression from 41.5 to 91.0% and survival time of 19 to 23 days. The first three combinations having lower levels of Aa (200 mg/kg) exhibited higher chemo suppression (> 90%) compared to Artemisinin-Lumefantrine positive control at 4 mg/kg with 87.5%. Lower levels of Aa in the combinations contributed to high chemo suppression while higher levels of Va prolonged survival times. Interactions between Aa and Mp showed higher chemo suppression, and that between Aa and Va increased survival time. An optimized prediction of 94.4% chemo suppression was made by the ANOVA model at lower levels of Aa and Va, and a higher level of Mp, which is similar to an experimental run which gave a response of 90. 6%. Conclusion An optimum combination of the three plants as a natural herbal antimalarial therapy was obtained using factorial design, and it offers an alternative to first line Artemisinin based Combination Therapy (ACTs) as parasite resistance looms. This combination could be further developed into a standard phytopharmaceutical and subjected to Randomized Controlled Trials (RCTs).